Evolving Resource-Based View: A Bibliometric Analysis of Firm Performance - Kendra Valentin; Tinik Sugiati; Ahmad Juliana (CV. Ulil Albab Corp, 2026)
The Resource-Based View (RBV) has long been a central framework for explaining firm performance heterogeneity, yet its static assumptions have been increasingly challenged by dynamic, digital, and sustainability-driven business environments. This study aims to systematically map the intellectual structure, thematic evolution, and key contributors of RBV research related to firm performance during the 2010–2025 period using a bibliometric approach. Drawing on 114 peer-reviewed journal articles retrieved from the Scopus database, the analysis employs VOSviewer and Bibliometrix to examine publication trends, leading sources, countries, institutions, influential authors, and keyword co-occurrence patterns. The findings reveal a significant resurgence of RBV research after 2018, accompanied by a clear shift from a focus on VRIN resources toward dynamic capabilities, sustainability-oriented resources, human capital, and stakeholder integration. Co-occurrence analysis further highlights the growing prominence of green innovation, ESG, and institutional contexts as strategic resources shaping firm performance. Overall, the study demonstrates that RBV has evolved into a more dynamic, sustainability-oriented, and context-sensitive framework, offering valuable insights for scholars and practitioners seeking to understand competitive advantage in complex and uncertain environments